Phytochemical Profiling, Antioxidant Activities And Effects Of Propolis Derived From Local Stingless Bee (Trigona Apicalis) On The Expression Of Adhesion Molecules In Endothelial Cells - Hapit, Nor Hussaini Abdul (2018)
Propolis is defined as a sticky, dark–coloured, resinous substance which produced by bees through combination of their saliva and plants exudates. Currently, there is substantial evidence indicating that propolis acquires many beneficial biological properties such as anti-bacterial, anti-fungal, anti-viral, anti-inflammatory, anti-ulcer, antioxidative and immunomodulating activities. This study aimed to analyze the phytochemical compositions of Trigona apicalis (T. apicalis) propolis from different location (B, M, S, K dan T) and evaluate their antioxidant and anti-inflammatory activities. Samples were extracted with an optimized extraction method,